2015
DOI: 10.1161/strokeaha.114.008323
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting Serum Autoantibodies Against the NMDAR Subunit NR1 Modulate Evolution of Lesion Size in Acute Ischemic Stroke

Abstract: Background and Purpose-Recently, we reported high seroprevalence (age-dependent up to >19%) of N-methyl-daspartate-receptor subunit NR1 (NMdAR1) autoantibodies in both healthy and neuropsychiatrically ill subjects (N=4236). Neuropsychiatric syndrome relevance was restricted to individuals with compromised blood-brain barrier, for example, apolipoprotein E4 (APOE4) carrier status, both clinically and experimentally. We now hypothesized that these autoantibodies may upon stroke be protective in individuals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
80
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 34 publications
6
80
1
3
Order By: Relevance
“…Classically, brain autoimmunity is mediated by IgG autoantibodies [38], which are rarely found in acute stroke. In contrast, the most frequently reported autoantibodies are of the IgM or IgA subclass [39].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Classically, brain autoimmunity is mediated by IgG autoantibodies [38], which are rarely found in acute stroke. In contrast, the most frequently reported autoantibodies are of the IgM or IgA subclass [39].…”
Section: Introductionmentioning
confidence: 92%
“…NMDAR1 autoantibodies seem to be beneficial or detrimental, depending on the BBB integrity before stroke. Using APOE4 carrier status as an indicator of a preexisting leaky BBB, Zerche et al [39] observed greater infarct growth in patients with BBB disruption and autoantibodies against NMDAR, whereas patients without previous BBB disruption that had autoantibodies showed the smallest infarct growth. Autoantibodies may also have a role in the development of poststroke cognitive impairment.…”
Section: Autoantibodiesmentioning
confidence: 99%
“…We agree that the role of endothelial NMdAR1 in blood-brain barrier (BBB) permeability and monocyte transmigration is intriguing. Also, the fact that in our study the modulating effects of NMdAR1-AB were less prominent in r-tPA (recombinant tissue-type plasminogen activator) as compared with non-r-tPA treated patients, despite their higher N number (see Figure IV), 1 may support an additional modifier influence of (exogenous) r-tPA on outcome that is probably independent of its thrombolytic activity. BBB integrity before stroke, however, at least tended to have the same influence regardless of r-tPA treatment: Beneficial NMdAR1-AB effects in individuals with previously intact BBB but harmful effects in APOE4 carriers with leaky BBB before the ischemic insult.…”
mentioning
confidence: 49%
“…1 The letter nicely extends the discussion on possible mechanisms of action that might contribute to the consequences of preexisting N-methyl-d-aspartate-receptor subunit NR1 (NMdAR1) autoantibodies (AB) on brain functions. We agree that the role of endothelial NMdAR1 in blood-brain barrier (BBB) permeability and monocyte transmigration is intriguing.…”
mentioning
confidence: 80%
“…The reported syndrome, reflecting typical NMDAR1 antagonistic actions, consisted of psychosis, epileptic seizures, dyskinesia, cognitive decline, reduced consciousness, and autonomic dysregulation [1][2][3][4]. However, work on >5000 individuals, healthy or affected by different diseases, consistently revealed overall comparable age-dependent seroprevalence of functional NMDAR1-AB of all Ig classes, nurturing serious doubts regarding a purely pathological role of NMDAR1-AB of any Ig class [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%